2020
DOI: 10.1093/mnras/staa2268
|View full text |Cite
|
Sign up to set email alerts
|

Powerful ionized gas outflows in the interacting radio galaxy 4C+29.30

Abstract: We investigate the ionized gas excitation and kinematics in the inner 4.3 × 6.2 kpc2 of the merger radio galaxy 4C +29.30. Using optical integral field spectroscopy with the Gemini North Telescope, we present flux distributions, line-ratio maps, peak velocities and velocity dispersion maps as well as channel maps with a spatial resolution of ≈955 pc. We observe high blueshifts of up to ∼−650 $\rm km\, s^{-1}$ in a region ∼1″ south of the nucleus (the southern knot – SK), which also presents high velocity dispe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…The final effect of the jet-ISM interaction depends on the jet power, the distribution of the surrounding medium, and its orientation with respect to the jet. In the merger radio galaxy 4C+29.30, Couto et al (2020) found a prominent outflow, with a total ionized gas mass outflow rate of 25 M yr −1 and an energy corresponding to ∼6 × 10 −2 of the AGN bolometric luminosity. A number of large-scale outflows of neutral hydrogen have been found mainly in young or restarted radio galaxies (identified by the blueshifted wings seen in HI absorption; see, e.g., Morganti et al 2003Morganti et al , 2005Morganti & Oosterloo 2018;Aditya & Kanekar 2018).…”
Section: Introductionmentioning
confidence: 92%
“…The final effect of the jet-ISM interaction depends on the jet power, the distribution of the surrounding medium, and its orientation with respect to the jet. In the merger radio galaxy 4C+29.30, Couto et al (2020) found a prominent outflow, with a total ionized gas mass outflow rate of 25 M yr −1 and an energy corresponding to ∼6 × 10 −2 of the AGN bolometric luminosity. A number of large-scale outflows of neutral hydrogen have been found mainly in young or restarted radio galaxies (identified by the blueshifted wings seen in HI absorption; see, e.g., Morganti et al 2003Morganti et al , 2005Morganti & Oosterloo 2018;Aditya & Kanekar 2018).…”
Section: Introductionmentioning
confidence: 92%
“…From the intrinsic (absorption-corrected) X-ray luminosity and [O III] luminosity, we estimate a radiative bolometric luminosity of ∼1-6 ×10 45 erg s −1 and an Eddington ratio of 5%, consistent with radiatively efficient accretion (Section 4.3). The bolometric luminosity, and associated Eddington ratio, calculated from the [O III] line is greater than that calculated from the X-ray luminosity, but it is unclear whether this result is due to the radio jet boosting the [O III] line luminosity (van Breugel et al 1986;Siemiginowska et al 2012;Couto et al 2020) or whether an inner, heavily Compton-thick ring of obscuration is causing the intrinsic X-ray luminosity deduced by the MYTORUS model to be underpredicted. The amount of kinetic energy carried by the jet (2.1 × 10 45 erg s −1 ) is comparable to that of the radiatively bolometric luminosity (Section 4.4).…”
Section: Discussionmentioning
confidence: 88%
“…The two outlier Sy 2 systems are likewise unique, with the presence of strong outflows or double-peaked narrow emission lines. Recent, optical integral field spectroscopy with the Gemini North Telescope (Couto et al 2020) for 4C+29.30 (BAT ID=426) indicated a large southern knot 1 south of the nucleus (and hence in the 3 SDSS fiber), which also presents high velocity dispersions (∼250 km s −1 ) attributed to an outflow. The other Sy 2 outlier, SDSS J000911.58-003654.7 (BAT ID=7), shows double-peaked narrow emission lines, and five nearby galaxies within 30 at similar redshift (< 500 km s −1 ), indicative of a galaxy group.…”
Section: D 25mentioning
confidence: 99%